Application of learning model with responsibility strategies in learning process at junior high school - Yusida Imran (International Conferences on Educational, Social Sciences and Technology)
This research is motivated by the existence of the phenomenon related with the problem of moral quality of students who are associated with learning, the lack of ability of learners in creativity. This study aims to develop a learning model with BMB-3 transformative strategy in the learning process at Junior High School in Padang City. This research is a model development research using ADDIE pattern. The location of this research is conducted in three junior high schools, public and private schools in Padang city, namely SMP Negeri 1 (accredited A), SMP 32 (accredited B), and SMP Angkasa Padang (accredited C), each class VIII. The instrument used in the form of the questionnaire, and data analysis is done quantitatively and qualitatively. Based on the results of research that has been done found the application of transformative strategy-BMB3 effectively used to improve the learning process.